Comparison of Epirubicin-Iodized Oil Suspension and Emulsion for Transcatheter Arterial Chemoembolization in VX2 Tumor. (12th March 2012) - Ueda, Tatsuo; Murata, Satoru; Mine, Takahiko; Onozawa, Shiro; Onda, Munehiko; Naito, Zenya; Amano, Yasuo; Kumita, Shinichiro
Abstract : To compare the antitumor efficacy and safety of transcatheter arterial chemoembolization (TACE) by epirubicin suspension (epirubicin suspension: epirubicin-iodized oil mixture without solution) to that by epirubicin emulsion (epirubicin emulsion: epirubicin-iodized oil mixture with solution), the efficacy of treatment by administration of either an epirubicin suspension or emulsion was examined in an animal model. Changes in plasma epirubicin concentration were compared over 24 h immediately after treatment, and enhanced ultrasonographic and histopathological analysis subsequently conducted 7 days after treatment to determine the growth ratio and proportion of viable tumor cells. The growth ratio and proportion of viable tumor cells were found to be significantly lower in the suspension group than in the emulsion group while the plasma epirubicin concentration was found to be significantly higher in the suspension group than in the emulsion group. These results indicate that administration of an epirubicin suspension is a superior form of TACE compared to that of administration of an epirubicin emulsion.